Heat transfer enhancement and pressure drop penalty in porous solar heaters: Numerical simulations. (January 2016) - Bovand, M.; Rashidi, S.; Esfahani, J.A.
Highlights: The pressure drop increases by increasing dimensionless porous layer thickness. The pressure drop increases by decreasing Darcy number. Nusselt decreases by increasing the porous substrate thicknesses for lower Darcy. The size of the thermally entrance zone increases with increase in Darcy number. The averaged Nusselt number increases by increasing radiation parameter. Abstract: A comprehensive numerical study is performed on the fluid flow and heat transfer within a porous solar heater. The effects of porous material on the heat transfer enhancement and pressure drop are presented in details. Also, the attention is focused on the effects of several parameters on the combined convection–radiation heat transfer and flow structures. Volume averaged equations are applied to simulate the transport phenomena within the porous substrate. Furthermore, the regular continuity, momentum, and energy equations are used in the clear fluid region. These equations are discretized using the control volume technique. It is found that the Nusselt number increases by inserting the porous substrate to the heater. These augmentations are up to 3, 4.4 and 5.9 times for δ  = 1/3, 2/3 and 1, respectively at Da = 10 - 2 . Also, the pressure drop increases with an increase in the porous layer thickness and decrease in the Darcy number.